OCCITANIA IN CATALONIA - E. . Grinina (Ибероамериканские тетради)
Annotated article focuses on the presence of Occitania in Catalonia. Both regions are linked old and close linguistic and cultural ties. Aran language (subdialects modern Occitan language), one of the three official languages of the Aran Valley in Catalonia, is a means of self-identification of the inhabitants of the Aran Valley, perceive themselves as occitans.